THE GOAL OF HPDSAR (HIGH PRECISION DENTAL SURGERY ASSISTING ROBOT) TO IMPROVE THE ACCURACY OF NON-INVASIVE ORAL CAVITY SURGICAL PROCEDURES - Goalbertus Goalbertus; Ho C.M. Brian (SYNTIFIC, 2026)
Background. The High Precision Dental Surgery Assisting Robot (HPDSAR), a novel, miniaturised system designed to revolutionise oral and maxillofacial procedures with paramount precision and minimal invasiveness. HPDSAR's operational superiority is established through an integrated system comprising advanced robotic auxiliary instruments and a Digital AI component. The system initiates with high-resolution imaging via CBCT scans and intraoral imaging, which is processed through deep learning mechanisms, specifically Convolutional Neural Networks (CNN), to generate a single, accurate surgical diagnosis. This study aim to determine the goal of HPDSAR to improve accuracy of non-invasive oral cavity surgical procedures. Research Method. This study used a scoping review approach to systematically map the scientific evidence related to the use of high-precision surgical robots (HPDSAR) in improving the accuracy of non-invasive surgical procedures in the oral cavity. Findings. The system incorporates haptic feedback and force-sensing to enhance the operator's control and prevent tissue damage, thus ensuring adherence to safety standards. By enabling minimally invasive surgery and drastically improving the visual field and procedural efficiency, HPDSAR offers significant medical advantages, leading to faster patient recovery and a reduced risk of complications such as post-operative infection and nerve damage, which are frequently reported in conventional oral surgery. Conclusion. In essence, HPDSAR represents a critical advancement, utilising a human-intelligence-mimicking system to deliver exceptional accuracy and performance in complex dental operative procedures.